Electro-hydrodynamic assisted mucoadhesive-floating beads containing black seed oil: development and characterization in-vitro and ex-vivo - Azad, Abul Kalam; Doolaanea, Abd Almonem; Al-Mahmood, Sinan Mohammed Abdullah (2019)
Background: Black seed oil (BSO) is attracting deep attention by scientific community due to its traditional therapeutic claim and pharmacological potential. Alginate widely used due to its biocompatibility, low cost and being a non-toxic polymer. Objective: The main objective of this study was to develop the BSO loaded mucoadhesive-floating beads with targeted size. Material and methods: BSO oil, alginate, lecithin and calcium chloride was used in this formulation. Electro-hydrodynamic assisted technique was employed to prepare BSO loaded alginate microsphere. The current study deals with the development, optimization, in-vitro characterization and ex-vivo mucoadhesive properties of BSO-loaded alginate beads. Results: The beads % of yield was determined. The optimized beads showed high drug encapsulation efficiency and suitable drug release pattern in simulated intestine media. The mean size and sphericity factor of the beads ranged from 0.75 ± 0.01 to 2.64 ± 0.01 mm and 0.05 ± 0.005 to 0.01 ± 0.00 mm respectively. It found to be dominant by Hixson-Crowell model (R2 = 0.983) with correlation coefficient close to unity over 2 h. The beads showed excellent floating behavior, insight of greater mucoadhesive properties and almost 100% swelling rate over 2 h in buffer media (pH 6.8). Conclusion: The technique for the preparation of beads containing BSO was found to be simple, reproducible, easily controllable, economical and consistent. Besides, the raw materials used for the formulation in this study such as sodium alginate, lecithin, calcium chloride and peppermint oil were cheap and easily available. This new approach to sustainable development goal is going to take a step forward, through a wider contribution to the pharmaceutical sector.